Influence of spiral pitch on the thermal behaviors of energy piles with spiral-tube heat exchanger. (October 2017) - Zhao, Qiang; Liu, Fang; Liu, Chunwei; Tian, Maocheng; Chen, Baoming
Highlights: Heat transfer of spiral-tube energy piles with four kinds of pitch was simulated. The thermal resistances and the heat transfer rates on pile surfaces were obtained. The g-functions of circulated fluid temperature were proposed for the four energy piles. The increase of pitch (SP = 0.25–2.0) lead to a reduction of COP (0.77–16.49%). Energy piles with a small pitch are energy-efficient and have better adaptability. Abstract: Energy pile is a cost-effective solution for ground-coupled heat pump systems to take the place of borehole ground heat exchanger partly. This paper focuses on the influence of spiral pitch on the transient thermal behaviors of an energy pile with spiral-tube heat exchanger. A transient 3D numerical model was established and solved by using the finite element method. The thermal resistances and the heat transfer rates were obtained and analyzed for the energy piles with four kinds of spiral pitch. The proposed g-functions of circulated fluid temperature were used to study fluid temperature and coefficient of performance based on the superposition method. As spiral pitch decreases, the change in both fluid temperature and internal thermal resistance diminishes but the change is narrowed down, although the total rate of the heat transfer on pile surfaces is almost same for all piles. For both heating and cooling, the difference between the extreme fluid temperatures diminishes and the mean coefficient of performance increases as spiral pitch decreases. The energy pile with a small spiral pitch is energy-efficient and has a better applicability. The increase of spiral pitch (SP = 0.25–2.0) leads to a reduction of the mean coefficients of performance (0.77–16.49%) according to the influential factors.